Observation of B0→D̄0K+K− and evidence for B0s→D̄0K+K− - Aaij, Roel; Adametz, Aleksandra; Bachmann, Sebastian; Bien, Alexander; Britsch, Markward; Blouw, Johan; Dordei, Francesca; Eisele, Franz; Färber, Christian; Gersabeck, Evelina; Hansmann-Menzemer, Stephanie; Hartmann, Tobias; et al. (Physical review letters, 2012)
The first observation of the decay B0→¯¯¯D0K+K− is reported from an analysis of 0.62 fb−1 of pp collision data collected with the LHCb detector. Its branching fraction is measured relative to that of the topologically similar decay B0→¯¯¯D0π+π− to be B(B0→¯¯¯D0K+K−)B(B0→¯¯¯D0π+π−)=0.056±0.011±0.007,where the first uncertainty is statistical and the second is systematic. The significance of the signal is 5.8σ. Evidence, with 3.8σ significance, for B0s→¯¯¯D0K+K− decays is also presented. The relative branching fraction is measured to be B(B0s→¯¯¯D0K+K−)B(B0→¯¯¯D0K+K−)=0.90±0.27±0.20. These channels are of interest to study the mechanisms behind hadronic B decays, and open new possibilities for CP violation analyses with larger data sets.
Im Titel sind "0" und "s" untereinander geschrieben: "s" ist tiefgestellt, "0" hochgestellt
Im Titel sind die Zeichen "null", "plus" und "minus" hochgestellt
The LHCb Collaboration: R. Aaij, A. Adametz, S. Bachmann, A. Bien, J. Blouw, M. Britsch,F. Dordei, F. Eisele, C. Fäber, E. Gersabeck, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, P. Krokovny, C. Langenbruch, C. Linn, J. Marks, M. Meissner, T. Nikodem, P. Seyfert, S. Stahl, J. v. Tilburg, U. Uwer, S. Wandernoth, D. Wiedner, A. Zhelezov [und weitere]
Gesehen am 24.10.2018